PWE-238 The prevalence of upper limb temperature dissociation in subgroups of FGID patients. (22nd June 2015) - Etherson, KJ; Emmett, C; Syme, P; Yiannakou, Y
Abstract : Introduction: Upper limb temperature dissociation has been demonstrated to exist in a prevalence of approximately 72% of FGID patients in our clinic, and in approximately 34% of controls. The prevalence of temperature dissociation in the subgroups of FGIDs are unknown. Aims: To assess the prevalence of upper limb temperature dissociation in FGID subgroups and compare against an expected prevalence previously demonstrated in controls. Method: Clinic attenders with a FGID diagnosis from a specialist tertiary clinic were sequentially invited to undertake the temperature sensation test. This comprised holding a bag of ice in both hands for 5 s and stating if they perceived the temperature to be either unilaterally colder or bilaterally equally cold. Unilaterally colder was considered to be evidence of upper limb temperature sensory dissociation. The actual percentage prevalence in each FGID subgroup was tested against an expected prevalence of 34.5% using a CHI-squared test with Fisher's correction where applicable. Results: Temperature sensory dissociation in the upper limbs was prevalent in most patients with FGIDs: 120/173 in the overall cohort (69%) [P < 0.0001], 79/109 with functional constipation (72.5%) [P < 0.0001], 10/13 with IBS-C (76.9%) [P = 0.001], 6/7 with IBS-D (85.7%) [P = 0.004], 7/10 with IBS-A (70%) [P = 0.018], 9/14 with gastropareisis (64.3%) [P = 0.018], 8/10 with functional vomiting (80%) [P = 0.002], and 6/9 with non-ulcer dyspepsia (67%) [P = 0.04]. There appeared to be no significant difference in patients with functional abdominal pain 7/14 (50%), and the rarer FGID subgroups were of an insufficiently small size to analyse. Conclusion: Upper limb temperature sensory dissociation appears to be significantly more prevalent in most subgroups of the FGIDs. This may imply a connexion with a central autonomic aetiology for these conditions. These results are an interesting observation from our clinic but are likely to be limited by inherent methodological biases in the data collection. Further investigation of the prevalence of temperature dissociation is required in both patients and controls in order to validate these findings. Disclosure of interest: None Declared.